Dampak Interaksi Anak yang Mengalami Speech Delay pada Anak 5 Tahun di Terapi Spisial Nasywa - Hijriati Hijriati; Amiratud Diana; Cut zahra iklima; Naura Finte Natte (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Speech delay is a term in English which means delay in speaking.Children who experience speech delay can have an impact on aspects of the child’s language development, thus also having an impact on the child’s social interaction abilities. This research using qualitative methods aims to find out the impact of children experiencing speech delay, and the role of teachers in handling children’s social interactions in Nasywa special therapy. The subjects of this research were a teacher and a 5 year old child who experienced speech delay. This type of qualitative descriptive research uses data collection techniques in the form of observation and interviews. The results of the research show that children are still not able to pronounce sentences clearly so that teachers can handle children’s interactions by responding and stimulating, using educational game tools such as puzzles, teaching children to practice pronouncing existing letters, teachers also provide additional learning that is equivalent to know more words, write letters, and communicate.